Prevalence of Urinary Tract Infections among First Grade Primary School Children in Gorgan, Northeast of Iran - Maryam Cheraghi; Mohammad Reza Zare; Mohammad Ali Vakili; Ali Akbar Hafezi; Arash Nikyar (Golestan University Of Medical Sciences, 2017)
ABSTRACT Introduction: The prevalence of urinary tract infection (UTI) in different regions of Iran is not clear. The aim of this study was to investigate the prevalence of UTI among first grade primary school children in Gorgan, Northeast of Iran. Materials and Methods: This descriptive-analytical and cross-sectional study was performed on 2145 first grade primary school children in the city of Gorgan in 2011. After history taking, all children were physically examined by trained personnel. Those who were suspected with UTI were referred to laboratory for confirmed diagnosis. Collected data were analyzed using SPSS statistical software (version 16) and chi-square test. Results: Among 2145 children, 1111 (51.8%) were male and the rest were female. UTI was confirmed in 146 patients (6.8%), 52 of whom were male (4.7%) and 94 were female (9.1%). There was a statistically significant difference in the frequency of UTI between the two genders. Conclusions: The results of this study showed that UTI is common in this age group in this region. Therefore, proper healthcare interventions should be considered for control and prevention of UTI complications among primary school children. KEYWORDS: UTI, Urinary tract infection, First grade, Primary school, Children, Gorgan